PENGARUH PAJAK TANGGUHAN, STRUKTUR MODAL DAN PERENCANAAN PAJAK TERHADAP KINERJA PERUSAHAAN - Dina lusiana; Muhammad ridwan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to empirically prove the influence of deferred taxes, capital structure and tax planning on company performance. This research was conducted at Consumer Goods sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research used is quantitative research. The type of data used is secondary data. Sampling was carried out using the purposive sampling method. The number of companies used as research samples was 16 companies with a research period of 5 (five) years, resulting in 80 samples. Data processing using Eviews 9 to analyze descriptive statistics, panel data regression estimation, panel data regression model selection, classical assumption test, panel data regression analysis, coefficient of determination (R2), F test or simultaneous test and t test or partial test. The results of this research show that Deferred Tax, Capital Structure and Tax Planning simultaneously have a significant effect on Return On Assets (ROA), Deferred Tax has no effect on Return On Assets (ROA), Capital Structure has a negative and significant effect on Return On Assets (ROA). And Tax Planning has a negative and significant effect on Return On Assets (ROA).